The truth project paper one—how did victims and survivors experience participation? Addressing epistemic relational inequality in the field of child sexual abuse - Barker, Claire; Ford, Stephanie; Eglinton, Rebekah; Quail, Sally; Taggart, Daniel (Frontiers in Psychiatry, 2023)
The last 30 years has seen an exponential increase in Historical Institutional Abuse Inquiries . One feature of these has been to place adult survivor voices at the center of Inquiry work, meaning that child abuse victims and survivors are engaging with Inquiries, sharing their experiences, with this participation often presented as empowering and healing. This initiative challenges long held beliefs that child sexual abuse survivors are unreliable witnesses, which has led to epistemic injustice and a hermeneutical lacunae in survivor testimony. However to date there has been limited research on what survivors say about their experiences of participation. The Truth Project was one area of work of the Independent Inquiry into Child Sexual Abuse in England and Wales. It invited survivors of Child Sexual Abuse to share their experiences including the impacts of abuse and their recommendations for change. The Truth Project concluded in 2021 and heard from more than 6,000 victims of child sexual abuse. The evaluation of the Trauma Informed Approach designed to support survivors through their engagement with the project was a mixed methods, two phase methodology. A total of 66 survey responses were received. Follow-up interviews were conducted with seven survey respondents. The Trauma Informed Approach was found to be predominantly helpful in attending to victim needs and minimizing harm. However, a small number of participants reported harmful effects post-session. The positive impacts reported about taking part in the Truth Project as a one-off engagement challenges beliefs that survivors of child sexual abuse cannot safely talk about their experiences. It also provides evidence of the central role survivors should have in designing services for trauma victims. This study contributes to the epistemic justice literature which emphasizes the central role of relational ethics in the politics of knowing, and the importance of developing a testimonial sensibility when listening to marginalized groups.